A Jew's best friend? : the image of the dog throughout Jewish history - Lieberman, Phillip I., 1970-; Zalashik, Rakefet, 1973- (Brighton ; Portland, Or. : Sussex Academic Press, 2013)
A discussion on the specific cultural manifestations of the relationship between dogs and Jews, from ancient times to the present, this work covers a geographical range extending from the Middle East through Europe and to North America, while the contributorsall of whom are senior university scholars specializing in various disciplinesprovide a unique cross-cultural, trans-national, diachronic perspective. An important theme is the constant tension between domination/control and partnership that underpins the relationship of humans to animals, as well as the connection between Jewish societies and their broader host cultures. A public increasingly interested in cultural history in general and Jewish history in particular will benefit from the diverse perspectives provided herein.
Chapter Eleven: Taking the Circumcised Dog by the Throat: A Critical Review of Contemporary Rituals for Dogs in America -- Aubrey L. GlazerChapter Twelve: Teaching the Jews and the Dog: A Pedagogical Essay -- Katharine Baker and Phillip Ackerman-Lieberman; The Contributors; Index.
The Lucius N. Littauer Book Fund.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Dogs -- Religious aspects -- Judaism; Dogs in the Bible; Dogs -- Social aspects; Human-animal relationships -- Religious aspects; Jews -- Social life and customs; Chiens -- Aspect religieux -- Judaïsme.; Chiens -- Aspect social; Juifs -- Mœurs et coutumes; RELIGION -- Judaism -- General; SOCIAL SCIENCE -- Anthropology -- Cultural; Dogs -- Religious aspects -- Judaism; Dogs in the Bible; Dogs -- Social aspects; Human-animal relationships -- Religious aspects; Jews -- Social life and customs; Criticism, interpretation, etc